Submaximal force production during perceptually guided isometric exercise - West, Sacha J.; Smith, Lynne; Lambert, Estelle V.; Noakes, Timothy D.; Gibson, Alan St Clair (European journal of applied physiology, 2005)
The aim of this study was to examine submaximal isometric force production guided by perceptual feelings of exertion. Thirty young adults performed isometric knee extensions on an isokinetic dynamometer. Subjects performed five different tests; the first test was the same for all subjects (standard naïve test). During the standard naïve test, subjects were asked to randomly produce force at perceived contraction intensities (25%, 50% and 75% of their maximum voluntary contraction (MVC)), with 100% MVC performed as the final intensity. All intensities, including the 100% MVC, were randomly performed in the other four tests (control tests 1 and 2, post 20% MVC and post 100% MVC tests). Post 20% MVC and post 100% MVC tests included fatiguing isometric exercise at 20% and 100% MVC respectively, which were performed prior to the test protocol. Results show that absolute peak force increased with increasing intensity (P<0.001) during all tests. During the standard naïve test, absolute peak force at 25% and 50% MVC was significantly lower (P=0.009) compared to control test 2, post 20% MVC and 100% MVC tests, and relative peak force was lower at all intensities compared to all other tests (P<0.001). Absolute and relative peak force was most accurate at 50% MVC (-12.06 N and -2.42%, respectively). Prior fatiguing isometric exercise did not affect the subsequent perceptual response range. In conclusion, isometric force was most accurate at 25% MVC but under-produced (perceptually overestimated) during higher contraction intensities preceding a maximal voluntary contraction (100% MVC). The ability to match absolute force with target contraction intensities was most accurate at 50% MVC during all five experimental conditions and poor at opposite ends of the force domain. Furthermore, prior fatiguing isometric exercise did not have an effect on the subsequent perceptual response range.